2023
DOI: 10.1111/jgs.18246
|View full text |Cite
|
Sign up to set email alerts
|

Competencies for video telemedicine with older adult patients

Abstract: Background Telemedicine has recently become a part of mainstream clinical practice. Many curricula have been developed to teach general and specialty‐specific video telemedicine skills; however, a lack of defined best practices for translating comprehensive interprofessional geriatric care to the virtual setting presents a unique challenge to educators and clinicians. This manuscript introduces and describes the development of competencies for video telemedicine with older adults for all health professionals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Patients’ physical and psychological comfort should be addressed to ensure a positive experience that respects patient beneficence and autonomy. Other studies have identified previsit preparation as an important clinician competency domain for video telemedicine with older adult patients, including optimizing the clinician environment for audibility and visibility and identifying who should be included in the visit and their roles in the patient’s care [ 26 ]. Our results echo privacy concerns in the telemedicine community regarding the sharing of sensitive information and diagnoses with care partners or others who happen to be in the appointment environment, which in some situations can pose distress to patients or caregivers [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients’ physical and psychological comfort should be addressed to ensure a positive experience that respects patient beneficence and autonomy. Other studies have identified previsit preparation as an important clinician competency domain for video telemedicine with older adult patients, including optimizing the clinician environment for audibility and visibility and identifying who should be included in the visit and their roles in the patient’s care [ 26 ]. Our results echo privacy concerns in the telemedicine community regarding the sharing of sensitive information and diagnoses with care partners or others who happen to be in the appointment environment, which in some situations can pose distress to patients or caregivers [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted interviews using the same VA videoconferencing platform used for clinical visits, enabling us to observe and interact with participants as they navigated technological and communication challenges and, if needed, provide necessary technical support or instruction. While other studies have examined satisfaction with telemedicine in older adults [ 9 , 10 ] and competencies of providers, including previsit preparation [ 26 ], few studies have looked in-depth at the experiences of older patients inexperienced in telemedicine as they prepare to engage in visits. We sought to (1) elicit patient and caregiver experiences attempting to participate in a video visit with a GRECC Connect geriatric specialist, and (2) explore facilitators and barriers to successful engagement in a telemedicine visit among this group.…”
Section: Introductionmentioning
confidence: 99%